2006
DOI: 10.1152/ajpendo.00331.2005
|View full text |Cite
|
Sign up to set email alerts
|

Stevioside counteracts the α-cell hypersecretion caused by long-term palmitate exposure

Abstract: Long-term exposure to fatty acids impairs beta-cell function in type 2 diabetes, but little is known about the chronic effects of fatty acids on alpha-cells. We therefore studied the prolonged impact of palmitate on alpha-cell function and on the expression of genes related to fuel metabolism. We also investigated whether the antihyperglycemic agent stevioside was able to counteract these effects of palmitate. Clonal alpha-TC1-6 cells were cultured with palmitate in the presence or absence of stevioside. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Contrary to the situation found in β-cells, long-term exposure to palmitate or oleate increases glucagon secretion of mouse and rat islets and αTC1-cells (Hong et al 2006(Hong et al , 2007 and abolishes the glucagonostatic effect of glucose (Collins et al 2008;Dumonteil et al 2000). These effects raise the question whether elevated plasma FFA levels may aggravate the hyperglucagonemia associated with type 2 diabetes.…”
Section: Fatty Acidsmentioning
confidence: 86%
“…Contrary to the situation found in β-cells, long-term exposure to palmitate or oleate increases glucagon secretion of mouse and rat islets and αTC1-cells (Hong et al 2006(Hong et al , 2007 and abolishes the glucagonostatic effect of glucose (Collins et al 2008;Dumonteil et al 2000). These effects raise the question whether elevated plasma FFA levels may aggravate the hyperglucagonemia associated with type 2 diabetes.…”
Section: Fatty Acidsmentioning
confidence: 86%
“…Stevioside, the parent compound of isosteviol, protects both α and β-cells against the effects of palmitate Hong et al, 2006). Furthermore, Hong et al (2006) suggested that the presence of palmitate contributes to stevioside's protective effects because in the presence of palmitate, stevioside enhances the gene expression of stearoyl-CoA desaturase (SCD). SCD converts palmitate to palmitoleate which is protective against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is interesting that plasma glucagons were decreased by 29% during the IAGTT in the stevioside-treated groups compared with the control group, and that the effect seems to be further enhanced when soy protein is added, where we found a lowering effect of 49%. Similarly, stevioside has recently been shown to reduce the palmitate-stimulated glucagon release from α-cells [28]. Clearly, SPI alone had no significant effect on glucagons.…”
Section: Discussionmentioning
confidence: 95%